Epidemiological and clinical characteristics of 35 children with COVID‐19 in Beijing, China. Issue 4 (28th December 2020) - He, Ming; Wang, Caiying; Xu, Lin; Zhang, Huimin; Liu, Yuhuan; Zhao, Yang; He, Shuxin; Zhang, Yanlan; Yang, Hongling; Liu, Yang; Miao, Min; Chen, Zhihai; et al.
ABSTRACT: Importance: Within the coronavirus disease 2019 (COVID‐19) global pandemic, more attention is warranted for whether this new infectious disease has unique manifestations in children. Objective: To retrospectively determine the epidemiological and clinical characteristics of 35 children with COVID‐19 in Beijing, China. Methods: We collected data for 35 children diagnosed with COVID‐19 who were admitted to Beijing Ditan Hospital from January 2020 to June 2020, and analyzed their epidemiological characteristics, clinical manifestations, laboratory examinations, chest imaging findings, treatments, and outcomes. Results: The children comprised 18 boys (51.4%) and 17 girls (48.6%) aged 6 months to 15 years. All patients had clear epidemiological history, with family clusters accounting for 28 cases (80.0%) and clear tracing of exposure to high epidemic areas in the remaining 7 cases (20.0%). Four (11.4%) patients were classified as asymptomatic, 17 (48.6%) as acute upper respiratory infection, and 14 (40.0%) as mild pneumonia, with no severe or critical cases. Clinical manifestations were mild, including fever in 18 (51.4%), cough in 14 (40.0%), and nausea and diarrhea in 7 (20.0%) patients. White blood cell count was mostly normal (26 cases, 74.3%) or decreased (7 cases, 20.0%); lymphocyte percentage was increased in 24 (68.7%); neutrophil percentage was decreased in 25 (71.4%); alanine aminotransferase was increased in 3 (8.6%); and serum potassium was decreased in 4 (11.4%). Time to negative viral nucleic acid testing was 2–42 days (mean: 14.0 ± 9.4 days). Chest imaging examination revealed that 20 patients (57.1%) had different forms of lung inflammation. Treatment was mainly isolation and nutritional support. Eleven patients were treated with interferon atomization inhalation. No patients required oxygen therapy. All 35 children were cured and discharged. Length of hospital stay was 9–54 days (mean: 25.4 ± 13.8 days). During regular follow‐up after discharge, 5 children showed positivity again in the viral nucleic acid test and were re‐hospitalized for observation and treatment. The mean length of re‐hospitalization stay was 10.8 days. Interpretation: Children with COVID‐19 mainly become infected within their family, and children of all ages are generally susceptible. The disease in children is mostly mild and the prognosis is good. Nucleic acid tests in some patients become positive again after discharge, suggesting that it is of great significance to carry out centralized isolation medical observations and active nucleic acid tests in close contacts for early detection of patients and routine epidemic prevention and control. Abstract : An overview of epidemiological and clinical characteristics of children with COVID‐19 in Beijing. About 14% of patients showed positive again in the viral nucleic acid test after discharge. This study are helpful for the prevention and control of COVID‐19 in children.